2018
DOI: 10.1590/1413-785220182601174568
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Joint Hipermobility on Postoperative Results of Knee Surgery

Abstract: Objective:To evaluate the prevalence of joint hypermobility in patients undergoing knee surgery to treat traumatic injury to the meniscus and anterior cruciate ligament, and the influence of this hypermobility on postoperative results. Methods:This prospective study assessed joint hypermobility in patients who underwent surgical reconstruction of the anterior cruciate ligament (ACL), partial meniscectomy, or a procedure combining ACL reconstruction and partial meniscectomy during the period 2011-2015. The Beig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
2
Order By: Relevance
“…The follow-up time was only 6 months and no correlation between hypermobility and the level of activity was found (table 5). 42…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up time was only 6 months and no correlation between hypermobility and the level of activity was found (table 5). 42…”
Section: Resultsmentioning
confidence: 99%
“…Only one study has evaluated return to sport, using the Tegner Activity Scale, and it found no correlation with GJH. However, in that study, return to sport was evaluated as early as 6 months postoperatively, making it difficult to draw any definitive conclusions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Outro estudo que não obteve uma representação positiva dos resultados foi abordado por Astur et al (2018) que cogitaram a influência da hipermobilidade quanto a recuperação pós-cirurgia do LCA, não sendo encontrada associação entre a hipermobilidade articular e as variáveis avaliadas, contudo a hipermobilidade também não mostrou impactos negativos quanto aos resultados pós-operatórios. Costa et al (2020) por meio de uma revisão sistemática da literatura, avaliou os efeitos da inclusão do treinamento proprioceptivo em diferentes desfechos, e não obteve evidências científicas satisfatórias que mostrassem os efeitos positivos da inclusão do tipo de treinamento estudado na pós-cirurgia de reconstrução do LCA.…”
unclassified
“…Características dos artigos da base de dados PubMed. abordagem elencada nos artigos da Tabela 3 apresenta possíveis tratamentos de LCA por meio da prevalência de hipermobilidade, práticas cirúrgicas especializadas e pela aplicação do treinamento proprioceptivo, desenvolvidos porAstur et al (2018),Arliani et al (2019) eCosta et al (2020) respectivamente. Características dos artigos da base de dados SciELO.Na Tabela 4 são apresentados 2 estudos com tratamentos que envolvem o trabalho de força isométrica, força máxima e equilíbrio de modo geral, propostos porPistone et al (2016) eSetuain et al (2016).…”
unclassified